K-Means Algorithm to Identify the Elderly Psychological Stress Analysis Algorithm - Yan Gao (Advances in Multimedia)
In order to study the psychological anxiety of the elderly, a psychological stress recognition algorithm based on ECG signal acquisition and heart rate variability was proposed based on the K-means algorithm. By collecting ECG signals of the elderly, HRV information can be accurately obtained, and RFC can be used to identify the psychological changes of the elderly under different degrees of stress. The research results show that the LR and RFC models have a better recognition effect on psychological stress when comparing with the KNN model. When the psychological stress is high, the test accuracy of the KNN model is 84.51%. The accuracy of stress recognition was 93.45%, and the accuracy of RFC’s recognition of psychological stress was 93.88%.